DEVELOPMENT OF ZSM-5 CATALYST VIA ZEOLITE BETA TRANSFORMATION FOR CATALYTIC OZONATION TREATMENT OF PHENOLIC WASTEWATER - Charisagabe Siagian, Xandra
Phenol compounds can be found in various industrial wastewater. However, phenol has high toxicity, making phenol waste classified as B3 waste that has detrimental effects on human health and ecosystem. One of the effective technologies for treating phenolic waste is catalytic ozonation. Among various kinds of catalysts, zeolite is one of the catalysts that has been widely used for catalytic ozonation processes. In this study, the development of the ZSM-5 catalyst synthesis method through interzeolite transformation with Beta zeolite as the parent zeolite will be reviewed. The main objective of this research is to develop an appropriate synthesis method to produce a catalyst with high phenol degradation efficiency. The research method used is an experimental method, quantitative analysis, and qualitative analysis. ZSM-5 is produced with ultrafast synthesis method, varying the synthesis time, and characterized using XRD, SEM, BET-BJH, and XRF methods. In addition, ZSM-5 is also tested for its activity in degrading phenol solution and the final concentration of the phenol is quantitatively analyzed with UV-Vis Spectrophotometer. ZSM-5 catalysts are successfully synthesized by this method based on the characterization results. The performance of ZSM-5 catalysts can degrade phenol up to 93% for under 1-hour reaction time. The difference in performance of the ZSM-5 catalysts is caused by the crystallite size and the pore volume of the zeolites.